Antibiotic-Loaded Hyperbranched Polyester Embedded into Peptide-Enriched Silk Fibroin for the Treatment of Orthopedic or Dental Infections - Zili Sideratou; Marco Biagiotti; Dimitris Tsiourvas; Katerina N. Panagiotaki; Marta V. Zucca; Giuliano Freddi; Arianna B. Lovati; Marta Bottagisio (Nanomaterials, 2022)
The development of innovative osteoconductive matrices, which are enriched with antibiotic delivery nanosystems, has the invaluable potential to achieve both local contaminant eradication and the osseointegration of implanted devices. With the aim of producing safe, bioactive materials that have osteoconductive and antibacterial properties, novel, antibiotic-loaded, functionalized nanoparticles (AFN)—based on carboxylic acid functionalized hyperbranched aliphatic polyester (CHAP) that can be integrated into peptide-enriched silk fibroin (PSF) matrices with osteoconductive properties—were successfully synthesized. The obtained AFNPSF sponges were first physico-chemically characterized and then tested in vitro against eukaryotic cells and bacteria involved in orthopedic or oral infections. The biocompatibility and microbiological tests confirmed the promising characteristics of the AFN-PSF products for both orthopedic and dental applications. These preliminary results encourage the establishment of AFN-PSF-based preventative strategies in the fight against implant-related infections.